Voice signal analysis techniques for cognitive decline (stress) assessment - Loizou, Christos P. (My University, 2026)
C. P. Loizou, P. Christodoulides, “Voice signal analysis techniques for cognitive decline (stress) assessment”, Journal of Physics: Int. Conf. on Engineering Systems (ICES 2020), Moscow, Russia, vol. 1687, no. 012007, pp. 1-8, 20-22 October 14-16, 2020.